2021
DOI: 10.1002/fsn3.2065
|View full text |Cite
|
Sign up to set email alerts
|

Comparing pH differential and methanol‐based methods for anthocyanin assessments of strawberries

Abstract: Anthocyanins are a group of water‐soluble polyphenolic pigments found primarily in flowers, vegetables, and fruits. These pigments play critical roles in plant and human health. Spectrophotometric methods are a simple and inexpensive way to quantify anthocyanins in plant tissues. Two main spectrophotometric methods have been developed, organic solvent‐based, and pH differential methods. Both of these methods are subject to interference from light‐absorbing impurities and need to be optimized for different matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 33 publications
(75 reference statements)
1
10
1
Order By: Relevance
“…Taghavi et al 27 have shown that the methanol:water method was better than the chloroform:methanol method for frozen strawberry samples, which is the opposite of what has been shown here, because water is a better solvent than chloroform for anthocyanins. With freeze-dried samples, there is no water in either the extraction buffer or the samples, the solubility of anthocyanins was limited to methanol, but a few anthocyanins dissolve in chloroform ( ie pelargonidin), and therefore, the anthocyanin yield was reduced.…”
Section: Resultscontrasting
confidence: 84%
See 4 more Smart Citations
“…Taghavi et al 27 have shown that the methanol:water method was better than the chloroform:methanol method for frozen strawberry samples, which is the opposite of what has been shown here, because water is a better solvent than chloroform for anthocyanins. With freeze-dried samples, there is no water in either the extraction buffer or the samples, the solubility of anthocyanins was limited to methanol, but a few anthocyanins dissolve in chloroform ( ie pelargonidin), and therefore, the anthocyanin yield was reduced.…”
Section: Resultscontrasting
confidence: 84%
“…The low anthocyanin content of the pH differential method was also seen in frozen strawberry samples. 27 The other downside of this method is the hazy anthocyanin solution produced that could not be completely clarified by either increasing the centrifugation time or even filtering. This method is extensively used by food scientists and horticulturists to assess the quality of fresh and processed fruits and vegetables.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations